Abuse of legal personality to avoid tax : piercing the corporate veil as remedy in case of the abuse of legal personality for tax purposes - Marais, Albertus Johannes (Stellenbosch : Stellenbosch University, 2019)
Thesis (LLD)--Stellenbosch University, 2019.